2014
DOI: 10.1371/journal.pgen.1004717
|View full text |Cite
|
Sign up to set email alerts
|

Role of abd-A and Abd-B in Development of Abdominal Epithelia Breaks Posterior Prevalence Rule

Abstract: Hox genes that determine anteroposterior body axis formation in all bilaterians are often found to have partially overlapping expression pattern. Since posterior genes dominate over anterior Hox genes in the region of co-expression, the anterior Hox genes are thought to have no function in such regions. In this study we show that two Hox genes have distinct and essential functions in the same cell. In Drosophila, the three Hox genes of the bithorax complex, Ubx, abd-A and Abd-B, show coexpression during embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 43 publications
8
26
0
Order By: Relevance
“…Consistently, we found that increased Pc activity led to disrupted tergite boundary formation ( Figure 2B), a phenotype that is linked with disturbance of homeotic genes (Karch et al, 1985;Breen, 1999;Wang et al, 2013;Singh and Mishra, 2014). When stx 2 somatic clones were induced, a similar tergite boundary defect was observed ( Figures 2C and 2D).…”
Section: Stx Genetically Interacts With Pcsupporting
confidence: 79%
“…Consistently, we found that increased Pc activity led to disrupted tergite boundary formation ( Figure 2B), a phenotype that is linked with disturbance of homeotic genes (Karch et al, 1985;Breen, 1999;Wang et al, 2013;Singh and Mishra, 2014). When stx 2 somatic clones were induced, a similar tergite boundary defect was observed ( Figures 2C and 2D).…”
Section: Stx Genetically Interacts With Pcsupporting
confidence: 79%
“…While overexpression of abd-A shows relatively stronger phenotypes described here, Abd-B overexpression does not. It supports our earlier finding in which we observed a non-homeotic growth promoter role of abd-A during formation of the adult cuticle during pupation, while Abd-B does not show any such role [46].…”
Section: Discussionsupporting
confidence: 92%
“…The offspring neurons thus generated selfassemble to form circuit architectures that mediate behaviors. The segmental boundary of anterior and posterior Wave neurons with distinct functional and morphological characteristics (Figure 4C) roughly corresponds to the expression boundary of the Hox gene Abd-B (Singh and Mishra, 2014). In the future, the study of command neurons such as the Wave neuron could inform us on how homologous neurons diverge in structure throughout development, possibly by differential recruitment of receptors for axon/dendrite guidance cues across segments under the regulation of Hox and other spatially restricted transcription factors (Hilliard and Bargmann, 2006;Lu et al, 2009).…”
Section: Lateral Interaction Between Distinct Command Systemsmentioning
confidence: 87%